Sinecatechins ointment as a potential novel treatment for usual type vulval intraepithelial neoplasia: a single‐centre double‐blind randomised control study. (8th November 2020) - Yap, J; Slade, D; Goddard, H; Dawson, C; Ganesan, R; Velangi, S; Sahu, B; Kaur, B; Hughes, A; Luesley, D
Abstract : Objective: To compare the safety and efficacy of 10% sinecatechins (Veregen ® ) ointment against placebo in the treatment of usual type vulvar intraepithelial neoplasia (uVIN). Design: A Phase II double‐blind randomised control trial. Setting: A tertiary gynaecological oncology referral centre. Population: All women diagnosed with primary and recurrent uVIN. Methods: Eligible patients were randomised 1:1 to receive either sinecatechins or placebo ointment (applied three times daily for 16 weeks) and were followed up at 2, 4, 8, 16, 32 and 52 weeks. Main outcome measures: The primary outcome measure, recorded at 16 and 32 weeks, was histological response (HR). Secondary outcome measures included clinical (CR) response, toxicity, quality of life and pain scores. Results: There was no observed difference in HR between the two arms. However, of the 26 patients who were randomised, all 13 patients who received sinecatechins showed either complete (n = 5) or partial (n = 8) CR, when best CR was evaluated. In placebo group, three patients had complete CR, two had partial CR, six had stable disease and two were lost to follow up. Patients in the sinecatechins group showed a statistically significant improvement in best observed CR as compared with the placebo group ( P = 0.002). There was no difference in toxicity reported in either group. Conclusion: Although we did not observe a difference in HR between the two treatment arms, we found that 10% sinecatechins application is safe and shows promise in inducing clinical resolution of uVIN lesions and symptom improvement, thus warranting further investigation in a larger multicentre study. Tweetable abstract: A randomised control study indicating that sinecatechins ointment may be a novel treatment for uVIN. Tweetable abstract: A randomised control study indicating that sinecatechins ointment may be a novel treatment for uVIN.